THE FOOD AND FEEDING HABITS OF THE GREY MULLETS, MUGIL PARSIA HAMILTON AND M. SPEIGLERI BLEEKER - Sarojini, K K (Indian Journal of Fisheries, 2016)
In an earlier paper, the author (Sarojini, 1951) reviewed the existing knowledge on the food and feeding habits of grey mullets and the diverse views held by previous workers. Three more contributions have since then been published in India, containing further information on this subject. Bapat and Bal*(1952) have stated that copepods constitute the main food of M. parsia in Bombay waters, which is supplemented by diatoms and organic matter taken along with mud